Micro-climatic survey of a Sugarcane field - Gadre, K.M. (MAUSAM, 1951)
The distribution of temperature and vapour pressure inside a sugarcane field during its various growth stages has been studied. It has been observed that in the earliest stages of crop the climate of the sugarcane field differs little from that of the open. The changes from the open to the crop are most rapid across the rows. The climate of the matured sugarcane crop becomes more or less uniform at within a distance of three row widths from the border.